The renewal of Tales of the Lagle Naaba on Burkina Faso’s national television service - Albert Ouédraogo (Tydskrif vir Letterkunde, 2019)
Thanks to the action of the Lagle naab a Abga, the evenings of folktales in villages were given a new lease of life on Burkina’s National Radio from the sixties. His grandson, the Lagle naab a Tigre, in collaboration with Henriette Ilboudo (presenter in the Mooré language on Burkina’s National Television) initiated soirées of folktales on the small screen. The introduction of the folktale on television is part of the political desire to promote the national cultural heritage and regional integration. The strong Burkinabè and mooréphone diaspora who retain links with Burkina Faso listen to national cultural productions. But the fact of using a medium like television to broadcast folktales brings about the violation of certain taboos (time of the narration, length of the performance and television space). Unlike evenings of folktales in the village, programmes that are recorded during the day and broadcast at night have a greater ability to enter homes that have a television set, both in Burkina and elsewhere in the world, thanks to satellites. The participants in the soirées of folktales usually wear traditional clothes and take care with their use of the Mooré language, avoiding words borrowed from French and the presence of modern objects on the set. The soirées of tales are a school in which moral values are applauded and deviant behaviour condemned, in order to build a society of peace and justice.